Genetic diversity of egg-carrying bunting, Adrianihcthys oophorus (Kottelat, 1990) endemic species of Lake Poso Central Sulawesi using truss morphometrics and sequens of cytochrome c oxidase subunit I gene (COI) - Wartono Hadie; Meria Tirsa Gundo; Lies Emmawati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2017)
Endemic fish acts as an indicator of a unique and useful fish species population as a key species in conservation efforts. Egg-carrying Buntingi (Adrianichthys oophorus) is an of endemic fish species in Poso Lake that needs to be protected from extinction.This study aims to evaluate the morphometric and molecular diversity of rono fish as a basis in the endemic fish conservation strategy. The samples of fish are collected from three populations, namely Tolombo, Taipa, and Ten-tena. A total of 30 fish collected samples from each location are morphometrically measured using the truss morpho-metric method and analyzed applying principle component analysis. The fish samples are molecularly analyzed DNA sequencing using COI. The result of the analysis shows that rono fish populations in Poso lake morphometrically and molecularly have different diversity. In morphometrics, there are 12 characters which are the basic characters of three rono fish populations (p> 0.05), as many as three characters will become characters adapting to an environment (p< 0.05), and 11 characters have adapted to an each environments (p< 0.01). The results of the morphometric and mole-cular analysis between the three populations are appearing synchronous. The Tentena population is different from other populations, showing a significant difference in DNA level. The implication of the results of this study indicates that the rono fish conservation strategy can be adopted by restoring the total gene pool. Gene pool recovery can be con-ducted through cross-breeding of three different populations, resulting in gene flow and increased fitness that will keep the population of rono fish as a sustainable endemic species. Abstrak Ikan endemik berperan sebagai indikator suatu populasi jenis ikan yang unik dan bermanfaat sebagai spesies kunci da-lam upaya konservasi. Ikan rono (Adrianichthys oophorus) adalah jenis ikan endemik di Danau Poso yang perlu dilin-dungi dari ancaman kepunahan. Penelitian ini bertujuan untuk mengevaluasi keragaman morfometrik dan molekuler ikan rono sebagai dasar dalam strategi konservasi ikan endemik tersebut. Sampel ikan dikoleksi dari tiga populasi, ya-itu populasi dari Tolombo, Taipa, dan Tentena. Sampel ikan sebanyak 30 ekor dari masing-masing lokasi diukur secara morfometrik menggunakan metode truss morphometric dan dianalisis dengan analisis komponen utama. Secara mole-kuler sampel ikan dianalisis sekuensing DNA menggunakan gen cytochrome C oxidase subunit 1 (COI). Hasil analisis menunjukkan bahwa populasi ikan rono di Danau Poso secara morfometrik dan molekuler memiliki keragaman yang berbeda. Secara morfometrik terdapat 12 karakter yang menjadi karakter dasar tiga populasi ikan rono (p> 0,05), seba-nyak tiga karakter akan menjadi karakter yang beradaptasi terhadap lingkungan (p < 0,05) dan 11 karakter telah bera-daptasi dengan lingkungan (p< 0,01). Hasil analisis morfometrik dan molekuler antar ketiga populasi terlihat sinkron. Populasi Tentena secara morfometrik dan molekuler terpisah dengan populasi lainnya yang berarti memiliki perbedaan nyata pada tingkat DNA dan morfometrik. Implikasi hasil penelitian ini memberikan indikasi bahwa strategi konservasi ikan rono dapat dilakukan dengan memulihkan kembali keragaman gen total (gen pool). Pemulihan gen pool dapat dila-kukan melalui perkawinan silang antar tiga populasi yang berbeda, sehingga terjadi aliran gen dan meningkatkan fitness yang akan menjaga populasi ikan rono sebagai jenis endemik tetap lestari.